Szójakészítménnyel gyártott húsipari termékek szójatartalmának meghatározása - Szabó Edith (Élelmiszervizsgálati közlemények, 1984)
A quick method suitable also for routine analytical purposes is presented by the author for the determination of the soybean content in products of the meat industry. The determination is based upon the volumetric determination of the hemicellulose content of the soybean amount added to the product. The prerequisite of the measurement is an accurate knowledge of the soybean species applied. The results obtained by means of his method and the accuracy of measurements are presented by the author. Eine rasche, auch zur rutinanalytische Zwecke verwendbare Methode wird vom Verfasser zur Bestimmung des Sojabohnengehaltes von Produkten der Fleischindustrie vorgelegt. Die Untersuchung beruht auf die volumetrische Bestimmung des Hemizellulosegehaltes der zugegebenen Sojabohne. Zur Messung ist eine genaue Kenntnis der Art des Sojaproduktes unentbehrlich. Die mittels der Methode erhaltenen Angaben und die Genauigkeit der Messung werden vom Verfasser beschrieben.